Length-Weight Relationship of Yellow Shrimp, Metapenaeus Brevicornis (Milne-Edwards, 1837), Along the Mumbai, Central Eastern Arabian Sea - Rinkesh N. Wanjari; Karankumar K. Ramteke; Dhanalakshmi M; B. B. Nayak; G. Deshmukhe (Journal of Indian Fisheries Association, 2023)
For the first time, a study was carried out on the length-weight relationship of the Metapenaeus brevicornis (Milne-Edwards, 1837) from the central-eastern Arabian Sea. The study was based on fortnightly experimental trawl fishing from August 2019 to November 2019. A total of 336 shrimp’s samples were measured. The length ranged between 5.21 and 10.19 cm while weight ranged between 9.9 and 22.0 gm. The results revealed a negative allometric growth pattern (mean "b" = 2.41 for pooled data). The correlation coefficient of total length with the body weight of shrimps was found to be high (r)=0.94 and r2=0.8831.